Substrate Integrated Waveguide on Glass with Vacuum-Filled Tin Through Glass Vias for Millimeter-Wave Applications - Seung-Han Chung; Ho-Sun Yeom; Che-Heung Kim; Yong-Kweon Kim; Seung-Ki Lee; Chang-Wook Baek; Jae-Hyoung Park (Micromachines)
This paper presents a novel approach to fabricate substrate integrated waveguides (SIWs) on glass substrates with tin (Sn) through glass vias (TGVs) tailored for millimeter-wave applications. The fabrication process employs a custom-designed vacuum suctioning system to rapidly fill precise TGV holes in the glass substrate, which are formed by wafer-level glass reflow micromachining techniques with molten tin in a minute. This method offers a very fast and cost-effective alternative for complete via filling without voids compared to the conventional metallization techniques such as electroplating or sputtering. An SIW with a 3-dB cutoff frequency of 17.2 GHz was fabricated using the proposed process. The fabricated SIW shows an average insertion loss of 1.65 ± 0.54 dB across the 20–35 GHz range. These results highlight the potential of glass substrates with tin TGVs for fabricating millimeter-wave devices.